Artrópodos componentes de la dieta de guajolotes de traspatio en el estado de Michoacán, México - Tobajas-Andrés, Fátima; Juárez-Caratachea, Aureliano; Pineda, Samuel; Figueroa, José Isaac (Instituto de Ecología, A.C., 2011)
This note presents the arthropods as part of the diet of creole turkeys reared in backyards. Fifty turkey crops collected from five physiographic regions of Michoacan were examinated; half of them collected during rainy season and the other half during dry season. Arthropods were found only in turkey crops obtained in rainy season, being adult and immature stages of insects (Hymenoptera, Hemiptera, Coleoptera, Lepidoptera) and myriapods (Diplopoda) the common groups component of the diet of backyard-reared creole turkeys.